Metal‐Based Nanocatalysts via a Universal Design on Cellular Structure. Issue 3 (26th November 2019) - Zhao, Yajing; Min, Xin; Ding, Zhengping; Chen, Shuang; Ai, Changzhi; Liu, Zhenglian; Yang, Tianzi; Wu, Xiaowen; Liu, Yan'gai; Lin, Shiwei; Huang, Zhaohui; Gao, Peng; et al.
Abstract: Metal‐based nanocatalysts supported on carbon have significant prospect for industry. However, a straightforward method for efficient and stable nanocatalysts still remains extremely challenging. Inspired by the structure and comptosition of cell walls and membranes, an ion chemical bond anchoring, an in situ carbonization coreduction process, is designed to obtain composite catalysts on N‐doped 2D carbon (C‐N) loaded with various noble and non‐noble metals (for example, Pt, Ru, Rh, Pd, Ag, Ir, Au, Co, and Ni) nanocatalysts. These 2 nm particles uniformly and stably bond with the C‐N support since the agglomeration and growth are suppressed by anchoring the metal ions on the cell wall and membrane during the carbonization and reduction reactions. The Pt@C‐N exhibits excellent catalytic activity and long‐term stability for the hydrogen evolution reaction, and the relative overpotential at 100 mA cm −2 is only 77 mV, which is much lower than that of commercial Pt/C and Pt single‐atom catalysts reported recently. Abstract : A series of metal‐based nanocatalysts is prepared through a universal design based on various cellular structures. These uniform noble and non‐noble metal nanoparticles, such as Pt, Ru, Rh, Pd, Ag, Ir, Au, Co, and Ni, stably bond with a N‐doped carbon support, which leads to an excellent catalytic activity and long‐term stability for the hydrogen evolution reaction.